Development of the eduka gantari website to improve literacy and numeracy in realizing the Profil Pelajar Pancasila - Robawati Robawati; Alifta Nurillah Kosasih; Riki Andriatna; Falach Noor Syahid; Sugiyani Sugiyani (University of Muhammadiyah Malang, 2025)
Literacy and numeracy as a manifestation of critical reasoning in the Profil Pelajar Pancasila an important role in life, including in elementary school students. However, the achievement of literacy and numeracy skills of students is still relatively low. The aim of this research is to develop digital learning media with the